Exploring the spectrum of gynaecological disorders in geriatric women: A hospital based cross-sectional study - Raguraman, S.; Balagobi, B.; Kumaran, S.; Jeyaluxmy, V.; Abirami, B.; Powsiga, U.; Shribavan, K. (University of Jaffna, 2024)
Background and objective: Elderly women suffer from gynaecological disorders due to ageing and hormonal changes in the post-reproductive period. However, there is inadequate evidence in Sri Lanka to deliver better care for geriatric women with gynaecological disorders. Therefore, we assessed the spectrum of gynaecological disorders among geriatric women in two out-patient settings at a tertiary hospital in northern Sri Lanka. Methods: A hospital-based descriptive cross-sectional study was conducted among 216 women aged 60 years and above who attended the gynaecology and urology clinics at the Teaching Hospital Jaffna. The data were collected using an interviewer-administered questionnaire and data extraction sheet. Analysis was performed in SPSS V26. The chi-square test was used to determine the association of sociodemographic factors with gynaecological disorders (significance level 0.05). Results: The mean age was 71.11±7.6 years, with the majority living in rural areas (60.2%). Common symptoms were lower urinary tract storage symptoms (77.3%), back pain (76.4%), and lumps at the vulva (74.1%). Less frequent symptoms included abdominal distension (27. 3%), postmenopausal bleeding (15.7%), and vulvar growth/ulcer (3.2%). Common comorbid conditions were hypertension (55.1%), diabetes mellitus (29.6%), and gynaecological conditions such as pelvic organ prolapse (uterovaginal prolapse 59.7%, cystocele 51.9%). Additionally, the study highlighted that 7.9% of women had postmenopausal bleeding with a benign cause, 6.9% had postmenopausal bleeding with a malignant cause in their endometrial assessment, and 13.4% had urogenital infections. There was a significant association between age and cystocele (p=0.004) and uterovaginal prolapse (p=0.007). Conclusion: Elderly women have notable gynaecological-related symptoms and disorders along with co-morbid conditions. By addressing the medical, social, and economic needs of elderly women, health systems can better support this growing demographic and improve their quality of life. The gynaecological disease burden in the geriatric group should be identified and addressed from the primary care level.
Keywords: Gynaecological disorders; Sri Lanka; Geriatric women; Pelvic organ prolapse